Identificación del nivel de gravedad de pancreatitis aguda a través del POP-SCORE predicción de resultados de pancreatitis en los pacientes atendidos en el Hospital Manuel Ygnacio Monteros - Seguro Social - IESS, en el periodo enero a junio de 2014 - Jaramillo Sánchez, Jorge Oswaldo (2015)
Acute pancreatitis is characterized by swelling and partial destruction of the pancreas, accompanied by a systemic inflammatory reaction that may cause complications and damage to other organs. Serious complications usually occur within the first 48 hours after admission, thereby being important to have simple tools to accurately predict the early stage and severity of this disease. The main objective was to identify the severity of acute pancreatitis through the POP-score (predicting outcome of pancreatitis) in patients treated at the hospital Manuel Ygnacio Monteros IESS social insurance. A cross-sectional study raises, the study population are patients with an established diagnosis of acute pancreatitis as score, who were hospitalized in the area of clinical hospital 2 Manuel Ygnacio Monteros - Social-IESS sure, in the period January to June 2014 . A higher scale score prediction result of pancreatitis (POP-score), predicting mortality will be higher, it was found that four patients with a score of 15-20, one of them entered the intensive care unit. The implementation of predicting outcome of pancreatitis (POP-score), within 24 hours of diagnosis of acute pancreatitis, is a predictor of severity. However, you should be aware of the intrinsic factors related to patients risk including: The patient's age, health problems of comorbidity, BMI, presence of systemic inflammatory response syndrome, signs of hypovolemia, among others.